دور التطبيقات المحاسبية السحابية في تحسين فعالية الوظيفة الجبائية في المؤسسة الجزائرية - فنغور، أحمد قاسم; عزيزي، نذير (جامعة الوادي University of Eloued, 2025)
The study illustrates the great importance of digital transformation in the field of accounting and collection through the role that smart applications have come to play through modern accounting techniques such as the SAP application in improving the functioning of the institution, including the fiscal function in the Algerian environment by controlling the performance of geometric obligations and tax compliance. The research has reached the following results: Compact accounting software applications made a difference in accounting work in terms of speed and accuracy. The application of the SAP system in Algerian institutions, which uses artificial intelligence, has improved the quality of the fiscal function through the following mechanisms: the promotion of accurate results thanks to automated input systems and automated calculations, the identification of powers and duties and the distribution of responsibilities. In conclusion, the summary indicates that digital transformation has a significant impact on the development of the field of accounting and the improvement of collection processes, thereby increasing the effectiveness of the fiscal function in the Algerian context and at a global level.
The Role of Cloud Accounting Applications in Improving the Effectiveness of Fiscal Function - Applied Study on SAP
مقال
Keywords: المحاسبة السحابية; الوظيفة الجبائية; الفعالية الجبائية; الرقمنة; Cloud Accounting; Digitization; Fiscal Function; Effectiveness; SAP Application